Literature Study: The Effectiveness of the Active Debate Method on Speaking Skills in Social Studies Subjects for Elementary School Students: Studi Literatur : Efektivitas Metode Debat Aktif Terhadap Keterampilan Berbicara Di Mata Pelajaran IPS Siswa Sekolah Dasar - Amalia Fadilah; Vanda Rezania (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine the effectiveness of the active debate method on students' speaking skills in the social studies subject at Elementary School, the type of research used in this thesis is using the type of literature study research. The research method used by the researcher is to collect research data in the form of library data that has been selected, searched for, presented and analyzed. The results of this study are the effectiveness of the active debate method affects the speaking skills of elementary school students, as evidenced by the results of the study: H1 is accepted and Ho is rejected, because H1 with p value < 0.05, so it can be concluded that the experimental class is better using the method debate because students can quickly hone their speaking skills, and can give students the ability to think logically, rationally, and make students more active and interactive in issuing an idea or opinion, so that it is easier for students to accept and think critically about questions. uttered by his interlocutor.